Integrating behavioral health and primary care: a qualitative analysis of financial barriers and solutions. Issue 3 (7th August 2020) - Shmerling, Alison C; Gold, Stephanie B; Gilchrist, Emma C; Miller, Benjamin F
Abstract: The objective of this study was to characterize financial barriers and solutions for the integration of behavioral health in primary care at the practice and system levels. Semi-structured interviews were conducted March–August of 2015 with 77 key informants. Initially a broad thematic coding approach was used, and data coded as "financing" was further analyzed in ATLAS.ti using an inductive thematic approach by three coders. Themes identified included the following: fragmentation of payment and inadequate investment limit movement toward integration; the evidence base for integration is not well known and requires appropriately structured further study; fee-for-service limits the movement to integration—an alternative payment system is needed; there are financial considerations beyond specific models of payment, including incentivizing innovation, prevention, and practice transformation support; stakeholders need to be engaged and aligned to support this process. There was consensus that the current fragmented, fee-for-service system with inadequate baseline reimbursement significantly hinders progression toward integrated behavioral health and primary care. Funding is needed both to support integrated care and to facilitate the transition to a new model. Multiple suggestions were offered regarding interim solutions to move toward an integrated model and ultimately global payment. Payment, in terms of both adequate amount and model, is a significant obstacle to integrating behavioral health and primary care. Future policy efforts must focus on ensuring stakeholder collaboration, multi-payer alignment, increasing investment in behavioral health and primary care, and moving away from fee-for-service toward a global and value-based payment model. Abstract : Payment, in terms of both amount and model, is an obstacle to behavioral health integration. Key informants comment on both interim- and longer-term solutions.